The Function and Mechanism of Long Non-coding RNA-ATB in Cancers - Xiao, Huizhong; Zhang, Fuyou; Zou, Yifan; Li, Jianfa; Liu, Yuchen; Huang, Weiren (Frontiers in Physiology, 2018)
Abstract: Long non-coding RNAs (lncRNAs) are a class of transcriptional RNA molecules with a length of greater than 200 nucleotides that function as regulatory factors in many human diseases. Studies have shown that long non-coding RNAs are involved in multiple cellular processes, including proliferation, apoptosis, migration, and invasion. In this report, a long non-coding RNA-ATB that is overexpressed in various tumor tissues and cell lines was investigated. Recent evidence suggests that ATB is dysfunctional in a variety of cancers, including hepatocellular carcinoma, gastric cancer, colorectal cancer, breast cancer, prostate cancer, renal cell carcinoma, non-small cell lung cancer, pancreatic cancer, osteosarcoma, and glioma. The high expression of ATB is associated with clinicopathological features of cancer patients. In addition, overexpression of lncRNA-ATB can promote tumor proliferation, migration, and invasion. LncRNA-ATB induces epithelial-mesenchymal transition by competitively binding to miRNAs, thus promoting tumor progression. Biological functions and mechanisms of ATB in human cancers are discussed here, concluding that lncRNA-ATB may provide a new biomarker for use in diagnosis and prognosis of cancer.